PENGARUH SERVICE QUALITY DAN CUSTOMER SATISFACTION TERHADAP CUSTOMER LOYALTY - Ruswanti, Endang (MAJALAH ILMIAH WIDYA, 2012)
Economy has a role similar quality service in the economy in developing countries but the impact is smaller than the total economyon service activities that encourage service providers to find the right method to please customers, the purpose of this paper is toachieve customer satisfaction is a concept well known and independent on some regions such as in the field of marketing, consumerresearch, economic psychology, economic well-being. The method used is based on the results of literature study. The conclusionis that satisfaction is the feeling that results from a process of evaluation about what is acceptable to what is expected to include athan the total economy on service activities that encourage service providers to find the right decision to purchase the goods themselves, as well as the need and desires of the associated purchase.